Macrophage-mediated cytotoxicity: role of a soluble macrophage cytotoxic factor similar to lymphotoxin and tumor necrosis factor. - Zacharchuk, C M (1983)
Guinea pig peritoneal macrophages, when activated for cytotoxicity by the calcium ionophore A23187 or lipopolysaccharide, produce a cytotoxic factor [macrophage cytotoxic factor (M phi-CF)] that is not blocked by catalase or protease inhibitors. Fractionation of culture supernates containing M phi-CF by gel filtration revealed one peak of cytotoxic activity of Mr approximately 45,000, the same as guinea pig lymphotoxin (LT). Antiserum prepared against purified guinea pig LT completely neutralized the cytotoxic activity of M phi-CF. In addition, the cytotoxic factor in guinea pig tumor necrosis serum was found to have a Mr of 45,000 and was neutralized by anti-LT. Thus, M phi-CF is physicochemically and immunochemically similar to LT and tumor necrosis factor, if not identical. To investigate the role of M phi-CF in macrophage-mediated cytotoxicity, anti-LT was added to A23187- or lipopolysaccharide-activated macrophages before addition of L-929 target cells. In 10 of 16 experiments, the inhibition of macrophage-mediated cytotoxicity was 100%. In the others, cytotoxicity was blocked partially, the lowest inhibition being 49%. The effectiveness of inhibition appeared to be inversely related to the intensity of macrophage activation. These results indicate that M phi-CF plays a significant role in macrophage-mediated cytotoxicity but involvement of another mechanism cannot be excluded.